2011
DOI: 10.1007/s12541-011-0141-5
|View full text |Cite
|
Sign up to set email alerts
|

Force coefficient at each support point of a container crane according to the wind direction

Abstract: This study is conducted to provide the force coefficient according to the wind direction from a wind tunnel test regarding the uplift force at each support point of a container crane and also the designed stowing devices -a tie-down rod and a stowage pin -and an alarm system to prevent overturning of the container crane under wind loads. In order to evaluate the effect of the wind load on the stability of the crane, two container cranes that are widely used in container terminals, viz., 50ton-class and 61ton-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Therefore, works that report the results of the measured wind conditions performed on real-scale structures are very important [20][21][22]. Next, these results are the basis for creating appropriate conditions in the aerodynamic tunnels, where the scaled models or parts of real-scale structures are investigated [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, works that report the results of the measured wind conditions performed on real-scale structures are very important [20][21][22]. Next, these results are the basis for creating appropriate conditions in the aerodynamic tunnels, where the scaled models or parts of real-scale structures are investigated [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…[1] This technology has been utilized for fabricating micro/nanostructures of metal, polymer, and DOI: 10.1002/admt.202301798 ceramic materials, etc. [2][3][4][5][6][7][8][9][10] A typical E-Jet printing setup mainly consists of a syringe pump, a needle, a high-voltage power supply, and a substrate. When a suitable electrical potential is applied to the nozzle, an electrostatic field is formed between the nozzle and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Current printing technologies used for electronics fabrication included fused deposition modeling, [ 24–26 ] stereolithography, [ 27,28 ] inkjet 3D printing, [ 29,30 ] etc. EHD printing has been studied as a cost‐effective, high‐resolution printing approach applied for a variety of functional materials, such as polymeric materials, [ 31,32 ] metal nanoparticles, [ 33 ] and molten metals, [ 5,10,34 ] which have been demonstrated for electronics fabrication. [ 35,36 ] Using soft substrates combined with proper fractal design offer excellent flexibility and stretchability for electronics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 35,36 ] Using soft substrates combined with proper fractal design offer excellent flexibility and stretchability for electronics. [ 5,10,34,37,38 ] A few previous research have demonstrated the fabrication of the metallic circuits embedded in the polymer structures, which can obtain stable electrical performance during deformation. [ 31,34,38–43 ] With the help of the supporting material or mechanical molds, conductors with 3D structures were fabricated by hybrid printing processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation